Manipulation and propaganda in the Russian media: The case of the Vriemia news programme (2017-2019) - Anna Llanos-Antczak; Zdzisław Śliwa (Contemporary Economics, 2021)
Information is a powerful tool used in any society and by any nation to create excepted perception of reality. Russian information operations have always been a very interesting example of using various media to manipulate international and domestic opinion in support of national (government) objectives. The situation has not changed in the contemporary information environment based on the nation's experiences and skilful utilization of emerging tools and technologies. Those capabilities are used pragmatically by Kremlin-controlled media to shape the future among younger people. In this respect, the paper is based on research conducted in selected Moscow and Saint Petersburg universities, responsible for educating future generations. The research is based on young adults' perception of the information provided by Channel One (Russian: ). This is the most influential and popular television channel controlled by the current government; therefore, it plays a significant role in spreading propaganda to shape the perception of the realm by domestic and foreign audiences alike. The authors conducted research in the years 2017-2019, employing the survey method to find out what is the effect of television-based propaganda type of information to manipulate the recipients. The research revealed that, although the Russian media strongly influences the study group, the respondents recognize the utilization of propaganda, which is founded on a one-sided narrative, and they are not easily manipulated. Moreover, the results presented that there is an interdependence between the favourable opinions about Channel One's Vriemia news coverage and vulnerability to manipulation and propaganda techniques.
Keywords: F59; 330; Vriemia; newscast; news programme; manipulation in mass media; propaganda